Pendampingan Pengembangan Usaha Mikro Kecil Menengah "Rona Surya" Melalui Penguatan Pemasaran Digital, Pembaruan Identitas Merek, dan Pengelolaan Keuangan Sederhana - Dida Maulidya Al Afshana; Akbar Marzuki Al Amin; Agung Winarno; Agus Hermawan (Jurnal Kabar Masyarakat, 2026)
Background:Micro, small, and medium enterprises (MSMEs) in Indonesia, particularly in the food processing sector, frequently encounter challenges such as limited production capacity, conventional marketing practices, weak brand identity, and inadequate financial documentation, which hinder sustainable business growth. This community service activity aimed to provide comprehensive assistance to Rona Surya, a traditional snack MSME located in Wagir, Malang Regency, through the formulation of production standard operating procedures (SOPs), digital marketing capacity building, brand identity renewal, human resource development, and simple financial recording training. The activity applied a participatory action approach involving direct observation, structured problem identification, systematic mentoring programs, and reflective evaluation over a 16-week period from January to May 2026. The program resulted in the development of a production SOP, active Instagram and TikTok accounts containing at least five promotional content items, a renewed brand logo, a business banner, a simple organizational structure, a vision and mission document, and a basic cash book. In addition, the business owner demonstrated measurable improvements in digital marketing capabilities, brand awareness management, and understanding the importance of separating personal and business finances.